Particle number, mass, and black carbon emissions from fuel-operated auxiliary heaters in real vehicle use. (December 2022) - Oikarinen, Henri; Olin, Miska; Martikainen, Sampsa; Leinonen, Ville; Mikkonen, Santtu; Karjalainen, Panu
Abstract: Fuel-operated auxiliary heaters (AHs) are frequent solutions to heat the vehicle engines and cabins in cold areas. Particulate exhaust emissions of AHs are unregulated; therefore, their contribution to local air quality and thus human health and even the global emissions budget is unknown. Experiments for studying the AH-originated emissions were performed under Finnish winter conditions mimicking real-world use for six selected vehicles with original AHs installed, including both gasoline- and diesel-powered heaters. We present quantitative results of particle number emissions down to 1.3 nm, particle size distributions, particulate mass, and black carbon, and compare to gaseous emissions. The start-up and shutdown phases showed the highest particle peaks, while the particle concentrations were stable between these. The mean particle number, mass and BC emission factors were found to be as high as 590 × 10 12 kgfuel −1, 33 mg kgfuel −1 and mg 18 kgfuel −1 for gasoline-operated heaters and 560 × 10 12 kgfuel −1, 20 mg kgfuel −1 and 12 mg kgfuel −1 for diesel-operated heaters. Comparing total number of particles larger than 23 nm emitted during vehicle preheating with AH to vehicle tailpipe emissions during drive shows that a typical heating cycle emits an equal number of particles to drive dozens or even thousands of kilometers. Highlights: Emissions from auxiliary vehicle heaters were measured under sub-zero conditions. Auxiliary heaters can be noteworthy sources of particle emissions from vehicles. Gasoline heaters produced mostly higher emissions than diesel heaters. Pre-heating particle emissions were comparable to driving of notably long routes.